Resilience to the effects of climate change on water resources and public health (Research, Society and Development, 2025)
The article examines how drought and intense rains, influenced by climate change, affect the availability of water resources and, consequently, public health, especially in Latin America with a focus on Ecuador. It identifies the impacts of these phenomena on agriculture, livestock, and access to drinking water, as well as their relationship with the increase in waterborne diseases and other health problems. The study also analyzes the resilience strategies implemented to mitigate these effects and protect vulnerable populations, highlighting the importance of intersectoral policies and the sustainable management of water resources. The objective of this systematic review is to analyze the impact of climate change on water resources, particularly in relation to drought and intense rainfall, and its impact on public health.